Residential green space and age at menarche in German and Australian adolescent girls: A longitudinal study - Markevych, Iana; Astell-Burt, Thomas; Altug, Hicran; Triebner, Kai; Standl, Marie; Flexeder, Claudia; Heinrich, Joachim; Schikowski, Tamara; Koletzko, Sibylle; Herberth, Gunda; Bauer, Carl-Peter; von Berg, Andrea; et al. (My University, 2022)
A large multicentre European study reported later onset of menopause among women residing in greener areas. This influence on the timing of a reproductive event like menopause, raises the question whether similar associations can be observed with timing of menarche. We investigated whether exposure to residential green space was related to the age at menarche in German and Australian adolescent girls. The analytic samples comprised of 1706 German and 1474 Australian adolescent girls. Percentage of green space was calculated in 1000 m buffers around a residential address or its surrogate at the previous follow-up. Mixed effects Cox proportional hazard models were used to explore the associations. The survival object was the occurrence of menarche at the time of follow-up (15-year follow-up of the German cohorts and the study wave at 14-15 years in the Australian cohort) and number of years since baseline (10-year follow-up in the German cohort and the study wave at 10-11 years in the Australian cohort). Participants who did not reach menarche were included as censored observations. A greener residence was not associated with the age at menarche. Null findings were consistent in the general population and in analyses stratified by socioeconomic status or urbanicity in both countries. Urban residents were more likely to have earlier menarche, and this association was consistent across Germany and Australia. The results of our analysis do not support the hypothesis that residing in places with more green space can influence timing of menarche. However, given the limitations of our study, researchers should not be discouraged to further explore environmental risk factors of early menarche.
International Journal of Hygiene and Environmental Health
Keywords: Adolescents and youth; Gender; Health and wellbeing; Housing, communities and neighbourhoods